Manufacturing processes of peanut (Arachis hypogaea) allergen powder-dnfp - Leonard, Stephanie A.; Ogawa, Yasushi; Jedrzejewski, Paul T.; Maleki, Soheila J.; Chapman, Martin D.; Tilles, Stephen A.; Du Toit, George; Mustafa, S. Shahzad; Vickery, Brian P. (Frontiers in Allergy, 2022)
Background: Important components of drug safety, efficacy, and acceptability involve manufacturing and testing of the drug substance and drug product. Peanut flour sourcing/processing and manufacturing processes may affect final drug product allergen potency and contamination level, possibly impacting drug safety, quality, and efficacy. We describe key steps in the manufacturing processes of peanut (Arachis hypogaea) allergen powder-dnfp (PTAH; Palforzia®), a drug used in oral immunotherapy (OIT) for the treatment of peanut allergy. Methods: Established criteria for source material must be met for manufacturing PTAH drug product. Degree of roasting was determined with a Hunter colorimeter. Protein/allergen content, identity, potency, safety, and quality of each batch of PTAH drug substance were assessed with a combustion analyzer, allergen-specific Western blot (immunoblotting), ELISA, and HPLC. Contaminants (ie, aflatoxin) were measured by UPLC. Results: Roasting degree beyond “light roast” was associated with variable degrees of protein allergen degradation, or potentially aggregation. Relative potency and amounts of protein allergens showed variability due in part to seasonal/manufacturing variability. Proportion of lots not meeting aflatoxin limits has increased in recent years. Up to 60% of peanut flour source material failed to meet screening selection acceptance criteria for proceeding to drug substance testing, mostly because of failure to meet potency acceptance criteria. Other lots were rejected due to safety (ie, aflatoxin) and quality. Influence of potency variation, within specification parameters, on safety/tolerability observed in trials was considered low, in part due to stringent controls placed at each step of manufacturing. Conclusions: Extensive variability in allergen potency is a critical issue during immunotherapy, particularly during OIT initial dose escalation and up-dosing, as it may result in lack of efficacy or avoidable adverse allergic reactions. Based on EU and US regulatory requirements, the production of PTAH includes manufacturing controls to ensure drug product safety, potency, and quality. For example, although PTAH contains all peanut allergens, each lot has met strict criteria ensuring consistent allergenic potency of Ara h 1, Ara h 2, and Ara h 6. The rigor of PTAH’s manufacturing process ensures reliable dose consistency and stability throughout its shelf life.